PADs and NETs in digestive system: From physiology to pathology - Song, Yi-Hang; Wang, Zhi-Jie; Kang, Le; He, Zi-Xuan; Zhao, Sheng-Bing; Fang, Xue; Li, Zhao-Shen; Wang, Shu-Ling; Bai, Yu (Frontiers in Immunology, 2023)
Peptidylarginine deiminases (PADs) are the only enzyme class known to deiminate arginine residues into citrulline in proteins, a process known as citrullination. This is an important post-translational modification that functions in several physiological and pathological processes. Neutrophil extracellular traps (NETs) are generated by NETosis, a novel cell death in neutrophils and a double-edged sword in inflammation. Excessive activation of PADs and NETs is critically implicated in their transformation from a physiological to a pathological state. Herein, we review the physiological and pathological functions of PADs and NETs, in particular, the involvement of PAD2 and PAD4 in the digestive system, from inflammatory to oncological diseases, along with related therapeutic prospects.